Comparing Scores From Full Length, Short Form, and Adaptive Tests of the Social Interaction Anxiety and Social Phobia Scales. (April 2020) - Sunderland, Matthew; Afzali, Mohammad H.; Batterham, Philip J.; Calear, Alison L.; Carragher, Natacha; Hobbs, Megan; Mahoney, Alison; Peters, Lorna; Slade, Tim
The current study developed and examined the performance of a computerized adaptive version of the Social Interaction Anxiety and Social Phobia Scales (SIAS/SPS) and compared results with a previously developed static short form (SIAS-6/SPS-6) in terms of measurement precision, concordance with the full forms, and sensitivity to treatment. Among an online sample of Australian adults, there were relatively minor differences in the performance of the adaptive tests and static short forms when compared with the full scales. Moreover, both adaptive and static short forms generated similar effect sizes across treatment in a clinical sample. This provides further evidence for the use of static or adaptive short forms of the SIAS/SPS rather than the lengthier 20-item versions. However, at the individual level, the adaptive tests were able to maintain an acceptable level of precision, using few items as possible, across the severity continua in contrast to the static short forms.